2008
DOI: 10.1158/1078-0432.ccr-07-5026
|View full text |Cite
|
Sign up to set email alerts
|

A Five-Gene Molecular Grade Index and HOXB13:IL17BR Are Complementary Prognostic Factors in Early Stage Breast Cancer

Abstract: Purpose: Histologic tumor grade is a well-established prognostic factor for breast cancer, and tumor grade^associated genes are the common denominator of many prognostic gene signatures. The objectives of this study are as follows: (a) to develop a simple gene expression index for tumor grade (molecular grade index or MGI), and (b) to determine whether MGI and our previously described HOXB13:IL17BR index together provide improved prognostic information. Experimental Design: From our previously published list o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
209
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 299 publications
(219 citation statements)
references
References 27 publications
4
209
0
6
Order By: Relevance
“…For instance, a recent meta-analysis of publicly available BC gene expression studies showed that the key biological drivers in nine prognostic signatures were proliferation related genes, in addition to ER signalling and ERBB2 amp lification [14]; results which have been reinforced by other authors [15]. As a consequence, attempts, such as genomic grade index (GGI) and mo lecular grade index (M GI), have been made to stratify grade 2 BC into lo w and high risk subgroups to imp rove clin ical relevance [16,17]. In their study, Sotiriou et al concluded that the gene signature characteristics displayed by grade 2 BC appears to be a mixture of signatures displayed by grade 1 and 3, rather than being independent or intermediate between t he two.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, a recent meta-analysis of publicly available BC gene expression studies showed that the key biological drivers in nine prognostic signatures were proliferation related genes, in addition to ER signalling and ERBB2 amp lification [14]; results which have been reinforced by other authors [15]. As a consequence, attempts, such as genomic grade index (GGI) and mo lecular grade index (M GI), have been made to stratify grade 2 BC into lo w and high risk subgroups to imp rove clin ical relevance [16,17]. In their study, Sotiriou et al concluded that the gene signature characteristics displayed by grade 2 BC appears to be a mixture of signatures displayed by grade 1 and 3, rather than being independent or intermediate between t he two.…”
Section: Introductionmentioning
confidence: 91%
“…In their study, Sotiriou et al concluded that the gene signature characteristics displayed by grade 2 BC appears to be a mixture of signatures displayed by grade 1 and 3, rather than being independent or intermediate between t he two. Moreover, the M GI appears to be as powerful prognostically as the GGI and relies only on five genes; all involved in different cell cycle phases, evaluated using quantitative PCR [17]. Ho wever, the co mplexity, quality assurance requirements and interpretation issues of expression array-based profiling and assays using nucleic acids (RNA and DNA) extracted fro m formalin-fixed paraffin embedded samples, coupled with its cost, potentially limit the use of this technology in the routine clin ical setting [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a small set of genes from differential expression profiles of several cancers has been used as a molecular signature for tumor diagnosis and prognosis in patients with urinary bladder cancer, breast cancer (Osman et al, 2006;de Reynies et al, 2009;Ma et al, 2008), adrenocortical tumor, colorectal cancer (Xu, et al, 2013) and intrahepatic CCA (Nishino et al, 2008;Kraiklang, et al, 2014). From the typical expression profile found in PBLs of CCA patients, we identified a set of three proteolytic related genes (PLAU, SERPINB2, CTSL) that when computed into "prognostic index", had significant power to predict the prognosis of CCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…For each case, three 10-mm tissue sections were cut, and an H&E slide was used to confirm 40% content of invasive cancer before manual macrodissection to enrich tumor content for RNA extraction. Total RNA was reverse transcribed and the resulting cDNA was preamplified using the PreAmp Master Mix Kit per the manufacturer's instructions (Applied Biosystems), followed by TaqMan RT-PCR as previously described (17). H/I, MGI, and BCI were calculated as described previously, blinded to all other variables (9,17,18).…”
Section: Breast Cancer Index Assaymentioning
confidence: 99%
“…Total RNA was reverse transcribed and the resulting cDNA was preamplified using the PreAmp Master Mix Kit per the manufacturer's instructions (Applied Biosystems), followed by TaqMan RT-PCR as previously described (17). H/I, MGI, and BCI were calculated as described previously, blinded to all other variables (9,17,18). Precision/reproducibility of the BCI assay was completed under quality system regulation (QSR) as part of the clinical laboratory (CLIA) quality management process and has been reported previously (9).…”
Section: Breast Cancer Index Assaymentioning
confidence: 99%